A Survey On The Prediction Of Exhaustion Attacks Over Wireless Networks Using Fuzzy Cluster Means (FCM) - Abdul Basith, K.; N.Shankar, T. (International Journal of Engineering and Technology, 2018)
The transmission of digital data from source to destination over wireless networks is challenging one due to noise and interferences. The noises can be negligible one or it may be avoided by increasing the transmission power, carrier strength and channel capacity. However, the interferences like hacking the information called attacks in wireless networks are unable to be avoided. This paper proposes the survey on the exhaustion attacks and DDoS attacks in wireless networks and also discuss about the security threats and the solutions to avoid the attacks.Â Â